2011
DOI: 10.1242/jcs.083485
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cζ binding to PtdIns(4,5)P2 requires the XY-linker region

Abstract: Phospholipase C-zeta (PLCζ) is a strong candidate for the mammalian sperm-derived factor that triggers the Ca2+ oscillations required for egg activation at fertilization. PLCζ lacks a PH domain, which targets PLCδ1 to the phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P2) substrate in the plasma membrane. Previous studies failed to detect PLCζ in the plasma membrane, hence the means of PLCζ binding to PtdIns(4,5)P2 is unclear. We find that the PLCζ XY linker, but not the C2 domain, exhibits robust binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…2, Table I). We have previously proposed that an unstructured positively charged cluster within the XY-linker region of PLCz may help anchor the protein to biological membranes through electrostatic interactions with the negatively charged PIP 2 (Nomikos et al, 2007;2011c Role of EF-hand domain in species potency of PLCz the XY-linker region of PLCz is poorly conserved among species (Saunders et al, 2007). Notably, the XY-linker of human PLCz is shorter in length and more positively charged than the mouse PLCz XY-linker, showing only 34.2% sequence identity and 18% similarity (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2, Table I). We have previously proposed that an unstructured positively charged cluster within the XY-linker region of PLCz may help anchor the protein to biological membranes through electrostatic interactions with the negatively charged PIP 2 (Nomikos et al, 2007;2011c Role of EF-hand domain in species potency of PLCz the XY-linker region of PLCz is poorly conserved among species (Saunders et al, 2007). Notably, the XY-linker of human PLCz is shorter in length and more positively charged than the mouse PLCz XY-linker, showing only 34.2% sequence identity and 18% similarity (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies showed that PLC acts on a distinct vesicular pool of PtdIns(4,5)P 2 within the egg cortex as opposed to the PM, showing clear distinction from PLC␦1 which affected the PM pool of the same lipid (1784). Also, unlike in other PLCs in which the linker region between the X-Y domains contains several acidic residues and exerts autoinhibition (612), in PLC this region contains a stretch of basic residues that mediate binding to membrane PtdIns(4,5)P 2 (1144), and removal of this region inhibits rather than activates the enzyme (1145). A basic stretch found within the X-domain has also been implicated in nuclear localization and nucleo-cytoplasmic shuttling of the enzyme during Ca 2ϩ oscillations (834).…”
Section: E Plcmentioning
confidence: 94%
“…In contrast, the PLCζ X-Y linker does not confer autoinhibition, but conversely appears to be required for maximal enzymatic activity [30]. Our studies indicate that positively charged residues within the PLCζ X-Y linker help target this enzyme to biological membranes via electrostatic interactions with the negatively charged substrate, PIP 2 [31,32]. The X-Y linker sequence of PLCζ is poorly conserved between species [3,4] and the significance of this X-Y linker diversity remains unclear.…”
Section: X-y Linker Region Mediates the Targeting Of Plcζ To Biologicmentioning
confidence: 77%
“…However, the exact role of the C2 domain in PLCζ function is unresolved. There is evidence for low-affinity binding of PLCζ C2 domain to membrane phospholipids; phosphatidylinositol 3-phosphate (PI-3P) and phosphatidylinositol 5-phosphate (PI-5P) [32,34]. It was suggested that C2 association with PI-3P may play a role in PLCζ targeting or regulation of activity, since the presence of PI-3P reduces in vitro PIP 2 hydrolysis by PLCζ [34].…”
Section: The C2 Domain Plays a Vital Role In Plcζ Functionmentioning
confidence: 99%